‘I am happy to be listened to’: co-creation of a simple tool to measure women’s experiences of respectful maternity care in urban Tanzania - Brenda Sequeira D’mello; Natasha Housseine; Hussein Lesio Kidanto; Nanna Maaløe; Jos van Roosmalen; Dan Wolf Meyrowitsch; Thomas van den Akker; Zainab Muniro; Evance Polin; Nuswe Ambokile; Charles Festo; Jane Brandt Sørensen; et al. (Global Health Action)
Background Rights-based Respectful Maternity Care (RMC) is crucial for quality of care and improved birth outcomes, yet RMC measurements are rarely included in facility improvement initiatives. We aimed to (i) co-create a routine RMC measurement tool (RMC-T) for congested maternity units in Dar es Salaam, Tanzania, and (ii) assess the RMC-T’s acceptability among women and healthcare stakeholders. Method We employed a participatory approach utilizing multiple mixed methods. This included a scoping review, stakeholder engagement involving postnatal women, healthcare providers, health leadership, and global researchers through interviews, focus groups, and two surveys involving 201 and 838 postnatal women. Cronbach’s alpha and factor analysis were conducted for validation using Stata 15. Theories of social practice and Thematic Framework of Acceptability guided the assessment of stakeholder priorities and tool acceptability. Results The multi-phased iterative co-creation process produced the 25-question RMC-T that measures satisfaction, communication, mistreatment (including physical, verbal, and sexual abuse; neglect; discrimination; lack of privacy; unconsented care; post-birth clean-up; informal payments; and denial of care), supportive care (such as food intake and mobility), birth companionship, post-procedure pain relief, bed-sharing, and newborn respect. The pragmatic validation process prioritized stakeholder feedback over strict statistics, lowering Cronbach’s alpha from 0.70 in version 1 to 0.57 for the RMC-T. Women valued the opportunity to share their experiences. Conclusions The RMC-T is contextualized, validated, and acceptable for measuring women’s experiences of RMC. Routine use in facility-based quality improvement initiatives, along with targeted actions to address gaps, will advance rights-based RMC. Further validation and community-based studies are needed.